Mycoplasma genitalium: a new kid on the block. Issue 3 (May 2017) - Reynolds‐Wright, John
Abstract : Mycoplasma genitalium, once thought to be a benign organism, is now considered a significant cause of non‐gonococcal urethritis. In this article the author describes how to identify infections and how to manage them.